2019
DOI: 10.1177/0300060519882563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of individual RONS in serum of smokers compared with non-smokers and their correlation with the lipid profile and antioxidant status

Abstract: Objective Cigarette smoking generates free radicals, such as reactive oxygen and nitrogen species (RONS) that contribute to many diseases. The aim of this study was to compare the levels of individual RONS in serum from smokers and non-smokers, and to examine their impact on lipid profiles and the endogenous antioxidant status, which is represented by vitamins C and E. Methods Ninety-four healthy Egyptian volunteers (48 smokers and 46 non-smokers) were enrolled. Blood samples were collected and analysed for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, the development of certain fluorescence-based probes has facilitated such measurements [20]. Thus, a recent study assessed individual ROS and RNS in the sera of rheumatoid arthritis patients [21] and healthy subjects that were smokers [22]. However, most of the research on ROS and RNS in COVID-19 patients has been focused on measuring overall oxidative stress rather than examining individual ROS and RNS and their related pathogenic functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of certain fluorescence-based probes has facilitated such measurements [20]. Thus, a recent study assessed individual ROS and RNS in the sera of rheumatoid arthritis patients [21] and healthy subjects that were smokers [22]. However, most of the research on ROS and RNS in COVID-19 patients has been focused on measuring overall oxidative stress rather than examining individual ROS and RNS and their related pathogenic functions.…”
Section: Introductionmentioning
confidence: 99%
“…One of these hypotheses states that nicotine stimulates the production and secretion of growth hormones, catecholamines and cortisol, which causes an increase in the serum concentrations of free fatty acids, which triggers the hepatic secretion of triglycerides and very-low-density lipoprotein (VLDL-C) [ 8 ]. In one study, Khojah and Ahmed found that smokers compared to non-smokers have higher levels of triglycerides, cholesterol, VLDL-C, low-density lipoprotein cholesterol (LDL-CHOL) and lower levels of high-density lipoprotein cholesterol (HDL-CHOL) [ 9 ]. The effects of chronic tobacco consumption (smoking and chewing) on the lipid profile of 75 individuals divided in three groups (I: non-smokers and non- chewers; II: smokers and non-chewers and III: chewers and non-smokers) were studied by Rao and Subash and the results showed that the levels of cholesterol, VLDL-C, LDL-CHOL and triglycerides were higher in group II and III compared to group I, and on the other hand, HDL-CHOL had decreased levels in the same groups of patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%